Implementation Of Financial Accounting Standards For Micro, Small And Medium-Sized Entities (SAK EMKM) On F&B MSMEs In Pontianak - Januari, Pamela Tri; Maulidia, Rahma; Desyana, Gita (SEAN Institute, 2024)
This research explores the financial reporting practices of Micro, Small, and Medium Enterprises (MSMEs) in Pontianak, specifically in the food and beverage sector, with a focus on their compliance with the Financial Accounting Standards for MSMEs (SAK EMKM). Utilizing a qualitative descriptive method, this study examines four MSMEs: Mie Rantau, Es Cendol Dahaga, Beefia Chizu, and Wonton Kak Mina. Data was collected through unstructured interviews, allowing for in-depth exploration of the financial recording systems used by these businesses. The study found that none of the MSMEs fully comply with SAK EMKM standards. Mie Rantau provides relatively comprehensive financial records but lacks the Notes to Financial Statements (CALK), a critical component for meeting SAK EMKM standards. Es Cendol Dahaga and Beefia Chizu maintain basic financial records, focusing primarily on daily income and expenses, but do not adequately track assets, liabilities, or inventory. Wonton Kak Mina has no formal financial reporting system, relying solely on simple income and expenditure tracking. The study identifies several factors contributing to this non-compliance, including the entrepreneurs' educational backgrounds and a lack of interest in detailed financial reporting. The findings suggest that while basic financial recording practices are in place, there is a significant need for greater awareness and education on the importance of comprehensive financial reporting in accordance with SAK EMKM. This research highlights the gap between current practices and the standards set by SAK EMKM, emphasizing the need for targeted support to help MSMEs improve their financial management and reporting practices.